Phosphodiesterase isoform-specific expression induced by traumatic brain injury - Oliva, Anthony A. (2012)
Traumatic brain injury (TBI) results in significant inflammation which contributes to the evolving pathology. Previously we have demonstrated that cyclic AMP (cAMP), a molecule involved in inflammation, is downregulated after traumatic brain injury (TBI). To determine the mechanism by which cAMP is downregulated after TBI, we determined whether TBI induces changes in phosphodiesterase (PDE) expression. Adult male Sprague Dawley rats received moderate parasagittal fluid-percussion brain injury (FPI) or sham injury, and the ipsilateral, parietal cortex was analyzed by western blotting. In the ipsilateral parietal cortex, expression of PDE1A, PDE4B2, and PDE4D2, significantly increased from 30 min to 24 hr post-injury. PDE10A significantly increased at 6 and 24 hr after TBI. Phosphorylation of PDE4A significantly increased from 6 hr to 7 days post-injury. In contrast, PDE1B, PD4A5, and PDE4A8 significantly decreased after TBI. No changes were observed with PDE1C, PDE3A, PDE4B1/3, PDE4B4, PDE4D3, PDE4D4, PDE8A, or PDE8B. Colocalization studies showed that PDE1A, PDE4B2, and phospho-PDE4A were neuronally expressed, whereas PDE4D2 was expressed in neither neurons nor glia. These findings suggest that therapies to reduce inflammation after TBI could be facilitated with targeted therapies, in particular for PDE1A, PDE4B2, PDE4D2, or PDE10A.